IMPLEMENTASI PERATURAN MENTERI PENDIDIKAN DAN KEBUDAYAAN NOMOR 75 TAHUN 2016 TENTANG KOMITE SEKOLAH PADA DINAS PENDIDIKAN PROVINSI SUMATERA SELATAN (STUDI KASUS PASAL 4 AYAT 1 DI SEKOLAH MENENGAH KEJURUAN NEGERI 2 PALEMBANG) - Ahmad Yani Kosali (Majalah Ilmiah Manajemen STIE Aprin Palembang, 2020)
The School Committee is an independent body of institution, formed based on democratic deliberations by educational stakeholders at the level of the education unit as a representation of verious elements responsible for improving the quality of the process and results of education. This study aims to determine how the implementation of Permendikbud Number 75 of 2016 concerning School Committees in the South Sumatra Province Educational Office ( Case Study Article 4 verse 1 in Vocational High School 2 Palembang ), and to find out the factors that support and hinder the implementation of Permendikbud Number 75 of 2016 concerning School Committees at the office of Education in South Sumatra province (Case Study Article 4 verse 1 in Vocational High School 2 Palembang). To clear illustrate the factors that have an important influences on the implementation of Permendikbud Number 75 of 2016 concerning School Committees in the South Sumatra Province Educational Office ( Case Study Article 4 Paragraph 1 in Vocational High School 2 Palembang ), the implementation model according to Marilee S. Grindle, where implementation is influenced by two big variables, namely : Policy Content and Implementation Environment. In this study, researchers used qualitative research. Informants in this study, namely : Chairperson of the School Committee as a key informant, while the Principal, Teachers, and Parents / Guardians of Students as supporting informants. Data collection techniques through : observation, interview, and documentation. Technical data analysis is done by data reduction, data presentation, and conclusion or data verification. Based on the analysis of researchers found that the implementation of Permendikbud Number 75 of 2016 South Sumatra Province ( Case Study Article 4 Paragraph in Vocational High School 2 Palembang ) in its implementation has been classified as good. Inhibiting factors in the participation of parents of students is still lacking, the difficulty in gathering parents because of the busy schedule of each parents. Supporting factors in the implementation of the School Committee include : strengthening the institutional committee of the School Committee, the organizational ability of the School Committee, establishing cooperation with related institution, and parents’ participation.